Exploiting physical defence traits for crop protection: leaf trichomes of Rubus idaeus have deterrent effects on spider mites but not aphids. (11th November 2015) - Karley, A.J.; Mitchell, C.; Brookes, C.; McNicol, J.; O'Neill, T.; Roberts, H.; Graham, J.; Johnson, S.N.
Abstract: Plants possess anti‐herbivore defences that could be exploited for crop protection. The potential for deploying physical defence traits for more sustainable pest management (i.e. reduced pesticide application) has not been fully realised. Using a perennial crop (red raspberry, Rubus idaeus ), we take the novel approach of quantifying within‐ and between‐genotype variation in a resistance trait, leaf trichome density, to determine precisely the effect of trichomes on host plant preference and suitability for two shoot‐feeding arthropods, the European large raspberry aphid ( Amphorophora idaei ) and two‐spotted spider mite ( Tetranychus urticae ). Additionally, we tested whether this trait influenced searching behaviour of a generalist herbivore predator (lacewing larvae, Chrysoperla carnea) . Although there was no consistent genotypic variation in R. idaeus suitability for T. urticae, our hypothesis that T. urticae would avoid high leaf trichome density was supported on certain genotypes. The deterrent effect was mainly on egg deposition rather than leaf selection by adults, with up to sixfold differences in leaf preference depending on the genotypes offered. By contrast, there was significant genotypic variation in R. idaeus suitability for A. idaei (10‐fold variation in aphid abundance), but, contrary to our prediction, aphid preference and infestation levels were unrelated to leaf trichome density. Instead, A. idaei performed best on vigorous genotypes, indicating that plant tolerance traits contributed to R. idaeus suitability for aphids. Leaf trichomes had little effect on the behaviour of the beneficial control agent C. carnea larvae. We conclude that physical anti‐herbivore defences, specifically leaf trichomes, could be deployed to deter particular arthropod pests. However, the mechanistic approach adopted here is necessary to avoid antagonistic effects on other pests or on natural enemies.